A Novel CRYBB2 Stopgain Mutation Causing Congenital Autosomal Dominant Cataract in a Chinese Family. (29th November 2016) - Zhou, Yu; Zhai, Yaru; Huang, Lulin; Gong, Bo; Li, Jie; Hao, Fang; Wu, Zhengzheng; Shi, Yi; Yang, Yin
Abstract : Congenital cataract is the most common cause of the visual disability and blindness in childhood. This study aimed to identify gene mutations responsible for autosomal dominant congenital cataract (ADCC) in a Chinese family using next-generation sequencing technology. This family included eight unaffected and five affected individuals. After complete ophthalmic examinations, the blood samples of the proband and two available family members were collected. Then the whole exome sequencing was performed on the proband and Sanger sequencing was applied to validate the causal mutation in the two family members and control samples. After the whole exome sequencing data were filtered through a series of existing variation databases, a heterozygous mutation c.499T<G (p.E167X) in CRYBB2 gene was found. And the results showed that the mutation cosegregated with the disease phenotype in the family and was absolutely absent in 1000 ethnicity-matched control samples. Thus, the heterozygous mutation c.499T<G (p.E167X) in CRYBB2 was the causal mutation responsible for this ADCC family. In conclusion, our findings revealed a novel stopgain mutation c.499T<G (p.E167X) in the exon 6 of CRYBB2 which expanded the mutation spectrum of CRYBB2 in Chinese congenital cataract population and illustrated the important role of CRYBB2 in the genetics research of congenital cataract.